PENINGKATAN MUTU PAPAN PARTIKEL MELALUI PENINGKATAN KADAR PEREKAT - M. I. Iskandar; Achmad Supriadi (BRIN Publishing, 2015)
The previous research of bagasse utilization from the sugar plant's waste for making boards using Urea Formaldehide (UF) as an adhesive up to 10%, resulted particle's boards with inferior physical and mechanical characteristics which could not fulfill the Indonesian standard. This paper investigates an improvement effort by increasing portion of adhesive to 12% and 14%. Results indicated that the boards had better quality than the previous research. All aspects of the improved particle's boards could fulfill standard of Indonesia, Japan and FAO, except thickness swelling and MOE values which are below the standard. There have been a clear tendency that a higher level of adhesive exerted a better quality, although particle boards characteristic were not affected by adesive level,except modulus of elasticity.